The economic expansion in the US since 2009 and Donald Trump's ambitions to 'drain the swamp' - Trevor Evans (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2018)
Since the prolonged recession in 1980–1982 which laid the basis for the emergence of finance-led capitalism in the US there have been four phases of economic expansion. The first three ended with increasingly severe recessions in 1990–1991, 2001 and 2007–2009. The most recent expansion, which began in mid 2009, has been characterised by relatively low growth and investment has been weaker than in previous expansions. Unemployment has fallen sharply, but many of the new jobs have been in low-paid services. The Trump government's much-touted investment programme is dependent on mobilising private funding but this has not yet been very forthcoming. Moves to relax the tighter banking regulations introduced in 2010, while strongly welcomed by the big banks, have been widely criticised. Key indicators of financial tensions are unusually low, but profitability and investment, which usually serve as leading indicators of the business cycle, have begun to decline and this suggests that the current expansion could be approaching an end.
Keywords: E25; E32; E44; E58; E65; F44; G01; 330; US economy; profitability; finance; wages; business cycle; crisis